Team efforts in the preparation and installation of the effigy - Mumbai Archive Project Team (Jio Institute, 2024)
The preparation of the effigy and the installation of decorations in Koliwadas bring together people from diverse backgrounds and communities, fostering a spirit of harmony and togetherness within the neighbourhood.